Thermoelectric Generator Efficiency Enhancement Through Copper Electrical Contact Optimization - N. Jagadesh Babu; Rajesh Kumar Burra (Ital Publication, 2026)
Thermoelectric generators (TEGs) can transform heat into electricity and have considerable potential for diverse applications. Nonetheless, their widespread use is limited by their low efficiency, mainly owing to their high internal electrical resistance. This study aims to improve TEG performance by reducing the electrical contact resistance through the application of copper. This study addresses the critical challenge of improving the performance of thermoelectric generators (TEG) by reducing the electrical contact resistance, which directly affects the output power and conversion efficiency, particularly at low temperatures. The main objective of this study was to investigate how the contact resistance influences the electrical conductance and overall energy conversion efficiency of TEGs and to optimize the contact geometries to enhance the performance. Copper contacts with different shapes (flat and circular) were designed and fabricated to evaluate their impact on electrical resistance. Experimental investigations using a commercial TEG module were conducted to measure the contact resistances and analyze their effects on electrical parameters, including the output voltage, power, and conversion efficiency. A comprehensive theoretical model was developed to assess the contact area, energy loss, and thermal factors. Equations were applied to quantify the contact resistance and its influence on the power output and efficiency. Notably, small circular copper contacts exhibited a significant reduction in contact resistance compared to flat contacts, leading to an 18.6% improvement in efficiency at low temperatures. This study demonstrates that optimizing the geometry and size of copper contacts can substantially reduce energy losses at the interfaces, thereby enhancing the current flow and boosting the TEG conversion efficiency. These findings provide a novel approach for addressing the prevalent issue of high internal resistance in thermoelectric devices, paving the way for more effective energy harvesting and waste-heat recovery. This study underscores the critical role of contact engineering in TEG technology and offers promising strategies for improving device efficiency and output power for future applications.